Hunting nature : Ivan Turgenev and the organic world - Hodge, Thomas P. (Ithaca : Cornell University Press, 2020)
"When we take seriously the effect Ivan Turgenev's lifelong passion for hunting had on his literary craft, we dramatically deepen our appreciation of the rich and complex ways one of Russia's most beloved writers depicted the natural world and the place of human beings within it"--
Introduction : The Hunting Writer : An Ecocritical Approach -- Catching Nature by the Tail -- The Gun Before the Lyre : Turgenev Afield -- "A Different Kind of Game" : Notes of a Hunter -- Thinking Oneself into Nature : The Aksakov Reviews and Their Aftermath -- Nature and Nidification : "Journey to the Forest-Belt," Rudin, A Gentry Nest -- Life at the Lek : On the Eve, "First Love," Fathers and Children -- Conclusion : "I'm a Sportsman": Deviations and Doubt.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 24, 2020).
In English.
JSTOR
Keywords: Turgenev, Ivan Sergeevich, -- 1818-1883 -- Knowledge -- Natural history; Turgenev, Ivan Sergeevich, -- 1818-1883 -- Knowledge -- Hunting; Turgenev, Ivan Sergeevich, -- 1818-1883 -- Criticism and interpretation; Turgenev, Ivan Sergeevich, -- 1818-1883 -- Criticism and interpretation; Turgenev, Ivan Sergeevich, -- 1818-1883 -- Knowledge -- Hunting; Turgenev, Ivan Sergeevich, -- 1818-1883 -- Knowledge -- Natural history; Turgenev, Ivan Sergeevich, -- 1818-1883; Hunting in literature; Nature in literature; Chasse dans la littérature.; Nature dans la littérature.; LITERARY CRITICISM / Russian & Former Soviet Union; Hunting; Hunting in literature; Natural history; Nature in literature; Electronic books; Criticism, interpretation, etc